2015
DOI: 10.1007/s00438-015-1054-2
|View full text |Cite
|
Sign up to set email alerts
|

Profiling gene expression in citrus fruit calyx abscission zone (AZ-C) treated with ethylene

Abstract: On-tree storage and harvesting of mature fruit account for a large proportion of cost in the production of citrus, and a reduction of the cost would not be achieved without a thorough understanding of the mechani sm of the mature fruit abscission. Genome-wide gene expression changes in ethylene-treated fruit calyx abscission zone (AZ-C) of Citrus sinensis cv. Olinda were therefore investigated using a citrus genome array representing up to 33,879 citrus transcripts. In total, 1313 and 1044 differentially regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 83 publications
1
21
0
Order By: Relevance
“…In other words, our data was consistent with mature citrus fruit abscission, which commenced with the activation of ethylene signal transduction pathway that led to the activation of ethylene-responsive transcription factors and the subsequent transcriptional regulation of a large set of ethylene responsive genes14. In soybean, ETH treatment significantly increased the abscission rate of flowers and pods.…”
Section: Discussionsupporting
confidence: 87%
“…In other words, our data was consistent with mature citrus fruit abscission, which commenced with the activation of ethylene signal transduction pathway that led to the activation of ethylene-responsive transcription factors and the subsequent transcriptional regulation of a large set of ethylene responsive genes14. In soybean, ETH treatment significantly increased the abscission rate of flowers and pods.…”
Section: Discussionsupporting
confidence: 87%
“…In citrus, it has been demonstrated that the shortage in carbohydrates triggers the abscission of fruitlets (June drop) through increasing the level of ethylene produced in fruit (G omez-Cadenas et al, 2000). By using exogenously applied ethylene and ethylene action inhibitor, a number of studies have provided evidence that, for healthy sweet orange trees, ethylene-induced abscission of mature fruit also involves up-regulation of the activity of hydrolytic enzymes as well as the expression of genes encoding these enzymes, including cellulase, PG, PL, PME, and members of the EXP transcription family (Burns and Lewandowski, 2000;Cheng et al, 2015;Goren and Huberman, 1976;Merelo et al, 2017). The results of this research demonstrated that ethylene biosynthesis genes ACS and ACO were not differentially expressed in any tissues of loose fruit compared with tight fruit, except for greater transcript levels of peel ACS and AZ-C ACO in loose fruit.…”
Section: Discussionmentioning
confidence: 99%
“…Sequences were obtained from GenBank and Reference Sequences databases [National Center for Biotechnology Information (NCBI), 2018b]. To determine the involvement of ethylene in HLB-associated preharvest fruit drop, the C. sinensis genes encoding enzymes catalyzing the ratelimiting steps for ethylene biosynthesis, ACS, and ACO (Liao and Burns, 2012), and an ERF1 (Cheng et al, 2015) were analyzed in AZ-C, peels, and leaves. Cellulase6 (CEL6), polygalacturonase 20 (PG20), pectate lyase5 (PL5), and EXP10 were selected to be analyzed in AZ-C because their expressions were correlated with the abscission process in ethylene-treated healthy sweet orange (Cheng et al, 2015;Merelo et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations